Flexible typesetting - Brown, Tim (Book Apart (Series), 2018)
For the first time in hundreds of years, because of the web, the role of the typographer has changed. We no longer decide; we suggest. We no longer simply choose typefaces, font sizes, line spacing, and margins; we prepare and instruct text to make those choices for itself. In this book, Tim Brown illuminates the complex, beautiful world of typesetting--arguably the most important part of typography because it forms the backbone of the reading experience--and shows us how to parry the inevitable pressures that arise when we can no longer predict how, and where, our text will be read.